Thrombin Promotes Matrix Metalloproteinase-13 Expression through the PKCδ/c-Src/EGFR/PI3K/Akt/AP-1 Signaling Pathway in Human Chondrocytes - Chun-Yin Huang; Hsiu-Jung Lin; Hsin-Shui Chen; Shi-Yann Cheng; Horng-Chaung Hsu; Chih-Hsin Tang (Mediators of Inflammation)
Thrombin is a key mediator of fibrin deposition, angiogenesis, and proinflammatory processes. Abnormalities in these processes are primary features of rheumatoid arthritis and osteoarthritis. Matrix metalloproteinase-13 (MMP-13) may contribute to the breakdown of articular cartilage during arthritis. However, the role of thrombin in MMP-13 production in chondrocytes is unknown. In this study, we investigated the intracellular signaling pathways involved in thrombin-induced MMP-13 expression in human chondrocytes. We found that stimulation with thrombin led to increased secretion of MMP-13 in cultured human chondrocytes. Further, this thrombin-induced MMP-13 production was reduced after transfection with siRNAs against protease activated receptors 1 and 3 (PAR1 and PAR3), but not with PAR4 siRNA. Treatment with specific inhibitors for PKCδ, c-Src, EGFR, PI3K, Akt, or AP-1 or with the corresponding siRNAs against these signaling proteins also abolished the thrombin-mediated increase in MMP-13 production in chondrocytes. Our results provide evidence that thrombin acts through the PAR1/PAR3 receptors and activates PKCδ and c-Src, resulting in EGFR transactivation and activation of PI3K, Akt, and finally AP-1 on the MMP-13 promoter, thereby contributing to cartilage destruction during arthritis.